Pembuatan Pemberat Kerucut Jaring Nelayan dari Bahan Timah Hitam 25 g, Kapasitas 30 Biji/Jam - Stevanus Nefa Ardian; Syamsul Hadi; Muhammad Madda Amrulloh; Chelista Aulia Marza; Muchammad Deni Satriyo Wardoyo (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
Floating and not sinking quickly fishing nets that have a small chance of catching fish are problems faced in the waters. The purpose of making is to obtain a cone weight with a length of 28.5 mm and a width of 28.5 mm, a height of 31 mm, 25 g of lead material totaling 80 pieces, around the fishing net made of nylon thread with a diameter of 1 mm, with a radius of 3 m, so that the number of weights becomes 2 kg and the weight of the net including the main rope is 3 kg which totals 5 kg. The manufacturing method includes: net weight design, making a mold containing 10 pieces of lead at a time, preparing lead material and casting equipment, casting lead into the mold, dismantling the mold and cutting the casting channel, connecting channels between weights and cutting risers, drilling 3 mm diameter weights, and checking the quality and dimensions of the net weights. The result of the production is a cone weight for fishing nets made of 25 g of black lead with a weight deviation of around 2 g, a total production cost of Rp. 950,-/piece, and a process duration of 2 minutes/piece which implies that for one fishing net 80 pieces can be installed with an estimated total weight of 2 kg of weight and a total weight of the net equipment of around 5 kg.